Proceedings of the 2nd Padang International Conference on Education, Economics, Business and Accounting (PICEEBA-2 2018) 2019
DOI: 10.2991/piceeba2-18.2019.40
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Convenience, Enjoyment, Perceived Risk, And Trust On The Attitude Toward Online Shopping

Abstract: The purpose of this research is to reveal the influence of convenience, enjoyment, perceived risk, and trust on the attitude of Padang State University students toward online shopping. Online and field surveys are conducted to collect data. A total of 242 questionnaires were analyzed using Structural Equation Modeling (SEM). The results show that convenience has a significant effect on enjoyment, then enjoyment has a significant effect on trust and attitude toward online shopping. Likewise with trust, this was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 45 publications
3
14
1
2
Order By: Relevance
“…When customers feel enjoyed, they are encouraged and motivated to take part in adopting and depending upon DCM for their travel decision‐making. This finding is in line with past studies of Gao and Bai (2014) and Marza et al (2018) in which PEJ is positively interlinked to consumers' attitude using online content for several purposes including shopping. Ryu and Murdock (2013) stated that PEJ has a positive impact on consumers' ATT toward mobile marketing communication and Cho and Son (2019) who revealed that people have a positive attitude toward online marketing and are engaged in information sharing.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…When customers feel enjoyed, they are encouraged and motivated to take part in adopting and depending upon DCM for their travel decision‐making. This finding is in line with past studies of Gao and Bai (2014) and Marza et al (2018) in which PEJ is positively interlinked to consumers' attitude using online content for several purposes including shopping. Ryu and Murdock (2013) stated that PEJ has a positive impact on consumers' ATT toward mobile marketing communication and Cho and Son (2019) who revealed that people have a positive attitude toward online marketing and are engaged in information sharing.…”
Section: Discussionsupporting
confidence: 92%
“…Hsu and Chang (2013) have extended the TAM model and revealed that consumers' attitudes are significantly impacted by the PCO of using technology. Additionally, Marza et al (2018) showed a positive relationship between attitude and PCO during online shopping. Based on the previous studies, the next hypothesis is formulated as follows:H7 Tourism consumers' attitudes are positively affected by the PCO of DCM.…”
Section: Review Of Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…The result of the test on hypothesis 2 in this study is different from that of the previous study [7]. However, the result of this study supports the research conducted by [23], in which perceived risk has no significant effect on consumer attitude. The risk faced is a mismatch between the expectations and reality received by consumers.…”
Section: Discussioncontrasting
confidence: 82%
“…The convenient factor significantly influences attitude with r=0.624, p=0.000. Empirically, past research has discovered that convenience has an influence on consumer enjoyment in using new media (Marza et al, 2018). Customers could feel the convenience in adopting the new media that facilitated their purchase intentions and it changes customers' attitudes more subtly through enjoyment.…”
Section: Resultsmentioning
confidence: 99%